Developing a video of tembang dolanan strengthen the character of grade IV students SDN 1 Ternyang - Vidya Cahya Dwi Citra Wardani; Cicilia Ika Rahayu Nita; Andika Gutama (Universitas Kanjuruhan Malang, 2026)
The limited availability of innovative learning media and low student engagement in Javanese language learning, particularly in tembang dolanan material, highlight the need for interactive learning resources. This study aimed to develop and validate an interactive learning video on tembang dolanan and its meanings for fourth-grade elementary school students. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The results showed that the developed video achieved high validity, with scores of 95% from media experts, 85.7% from language experts, and 97.5% from material experts. The practicality score reached 95% based on teacher and student responses. The implementation of the video resulted in an average N-Gain score of 0.95, indicating high effectiveness. Therefore, the learning video is valid, practical, and effective for supporting Javanese language learning and enhancing students’ learning outcomes.